A Hoogsteen base pair embedded in undistorted B-DNA - Aishima, Jun (Oxford University Press, 2002)
Hoogsteen base pairs within duplex DNA typically are only observed in regions containing significant distortion or near sites of drug intercalation. We report here the observation of a Hoogsteen base pair embedded within undistorted, unmodified B-DNA. The Hoogsteen base pair, consisting of a syn adenine base paired with an anti thymine base, is found in the 2.1 Å resolution structure of the MATα2 homeodomain bound to DNA in a region where a specifically and a non-specifically bound homeodomain contact overlapping sites. NMR studies of the free DNA show no evidence of Hoogsteen base pair formation, suggesting that protein binding favors the transition from a Watson–Crick to a Hoogsteen base pair. Molecular dynamics simulations of the homeodomain–DNA complex support a role for the non-specifically bound protein in favoring Hoogsteen base pair formation. The presence of a Hoogsteen base pair in the crystal structure of a protein–DNA complex raises the possibility that Hoogsteen base pairs could occur within duplex DNA and play a hitherto unrecognized role in transcription, replication and other cellular processes.